Corporate currency risk and hedging in Chile: Real and financial effects - Roberto Álvarez Espinoza; Erwin Hansen (Inter-American Development Bank (IDB), 2017)
This paper examines a panel (1994-2014) of Chilean non-financial firms, both publicly listed and private, which was built to analyze the determinants of the use of foreign currency debt and their potential consequences for firm investment and profitability. It is found that foreign assets and the use of FX derivatives are positively associated with firms' use of foreign currency debt. Also, depending on the estimation method, exports appear as an important determinant of the use of foreign currency debt. In terms of the potential effect of holding foreign currency debt on firms' performance after an exchange rate devaluation, no statistical differential effect is identified on either firm profitability or firm investment. This (lack of) result is interpreted as evidence that firms match liabilities and assets denominated in foreign currency and that firms actively involved in hedging aim to reduce their exposure to foreign exchange fluctuations.
hdl:11319/8191
Keywords: F34; G31; E22; 330; Foreign currency debt; Currency mismatch; Balance sheet effect; Chile